2022
DOI: 10.1111/cas.15616
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative rapid immunohistochemistry with noncontact antibody mixing for undiagnosed pulmonary tumors

Abstract: Knowledge of the histologic type and primary origin of pulmonary tumors is essential when preparing a surgical strategy. Intraoperative diagnosis of hematoxylin and eosin (H&E)-stained frozen sections is the gold standard, but reliable pathology requires time-consuming immunohistochemistry (IHC) to distinguish among histological types/organ origins and to analyze molecular status. The aim of this study was to evaluate the clinical reliability of a new rapid-IHC technique for intraoperative diagnosis of pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The further increase in the importance of surgical procedures for the treatment of localized tumors will pose particular challenges for the intraoperative classification of lung tumors. In particular, the differentiation of preinvasive from early invasive lesions in frozen sections is currently a field of intensive work in pathology [ 33 ] with the aim of implementing intraoperative immunohistological techniques [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The further increase in the importance of surgical procedures for the treatment of localized tumors will pose particular challenges for the intraoperative classification of lung tumors. In particular, the differentiation of preinvasive from early invasive lesions in frozen sections is currently a field of intensive work in pathology [ 33 ] with the aim of implementing intraoperative immunohistological techniques [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…18,19 However, maintaining a constant temperature in an incubator is challenging, and using a microwave can cause the section to dry. Japanese scholars have applied alternating current to accelerate the reaction, 8,20 and ultrasound irradiation has been shown to shorten the antibody reaction time. 19 However, these techniques require specialized equipment and involve potential electrical hazards.…”
Section: Discussionmentioning
confidence: 99%
“…A false negative rate of 2%–13.1 % and false positive rates of 0%–0.2 %, compared to definitive pathology results, are among the most important problems of FS [ 17 , 18 ]. In a study of 1000 patients involving all tissue types, Oneson et al [ 19 ] reported an overall accuracy rate of 91 %, a false negativity rate of 2 % and a false positivity rate of 0.2 % for FS examination, while an FS examination did not yield a prediagnosis in 6 % of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In another multicenter study involving approximately 80,000 patients, the final diagnosis was pending in 4.2 % of the patients until the results from paraffin-embedded tissue blocks became available, while the overall concordance of the FS diagnoses with the final diagnoses was 98.3 % in the patients for whom the FS examination suggested a diagnosis [ 11 ]. Imai et al in their series of 169 patients with undiagnosed lung tumors, reported the overall definitive diagnosis rate of FS, the rate of identified tumor origin, and the rate of identified histological type as 76.92 %, 85.80 %, and 90.53 %, respectively [ 17 ]. In a study by Gephardt et al involving a series of 122 patients with lung cancer, the sensitivity, specificity and false negativity rates reported for intraoperative FS examinations of the lymph nodes were 95 %, 100 % and 1.6 %, respectively [ 21 ].…”
Section: Discussionmentioning
confidence: 99%